Risk management committee characteristics and audit report lag: evidence from Malaysia - Abdellatif Ismaiel, Abdelhamid Elsayed (2020)
The timeliness of audited financial reporting is valuable to deliver relevant information to stakeholders at the appropriate time, which will alleviate the decisions-related uncertainty, and also represents an indicator of the quality of corporate transparency. While audit delay adversely affects the delivery of timely financial statements. Given that effective board committees represent the major internal corporate governance mechanisms, this highlights the potential effects of the risk management committee (RMC), as a sub-committee, on the determination of audit report lag (ARL). Hence, the study aims to investigate the association between the RMC characteristics; RMC size, RMC independence, RMC diligence (meetings), and accounting and industry expertise of the RMC chairperson with ARL. Drawing on the agency theory, four hypotheses are tested using data collected from the year 2018 annual reports for the 184 non-financial listed companies, which compose a board-level RMC, on Bursa Malaysia. The descriptive results show that the extent of ARL for the sample selected is an average of 97 days and ranges from a minimum period of 45 days to a maximum period of 122 days. Ordinary Least Square (OLS) regression was employed to prove the hypotheses. The results reveal that RMC diligence, accounting and industry expertise of the RMC chairperson, corporate size, investment opportunities, and nonaudit fees are significantly and negatively associated with ARL, while firm performance (loss) has a significantly positive relationship with ARL. Meanwhile, RMC size, RMC independence, board size, audit committee meetings, financial condition, auditor type, and audit fees are insignificantly related to audit delay. The study empirically contributes to the existing literature regarding ARL, especially on the influences of RMC characteristics on ARL. Practically, it also provides useful information for policymakers and practitioners to pay more attention to the vital role of well-structured and functioning RMC in improving the timeliness of financial reporting.